2018
DOI: 10.1186/s12939-018-0863-4
|View full text |Cite
|
Sign up to set email alerts
|

“I attend at Vanguard and I attend here as well”: barriers to accessing healthcare services among older South Africans with HIV and non-communicable diseases

Abstract: BackgroundHIV and non-communicable disease (NCD) are syndemic within sub-Saharan Africa especially among older persons. The two epidemics interact with one another within a context of poverty, inequality and inequitable access to healthcare resulting in an increase in those aged 50 and older living with HIV and experiencing an NCD co-morbidity. We explore the challenges of navigating healthcare for older persons living with HIV and NCD co-morbidity.MethodsIn-depth semi-structured interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…The cost of seeking care for multiple conditions, often offered by different healthcare providers and likely on different days was not only expressed as being expensive but also hinders continuous HIV care seeking. Our findings concur with previous studies [36,[38][39][40][41][42] conducted in developing countries including studies done by researchers in Uganda's MRC/UVRI that indicate continuous struggle faced by older adults managing HIV and other chronic diseases. Distance to the facility, cost of traveling to access care, and time [36,42] have all been cited as barriers to accessing HIV care services among HIV infected older adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cost of seeking care for multiple conditions, often offered by different healthcare providers and likely on different days was not only expressed as being expensive but also hinders continuous HIV care seeking. Our findings concur with previous studies [36,[38][39][40][41][42] conducted in developing countries including studies done by researchers in Uganda's MRC/UVRI that indicate continuous struggle faced by older adults managing HIV and other chronic diseases. Distance to the facility, cost of traveling to access care, and time [36,42] have all been cited as barriers to accessing HIV care services among HIV infected older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings concur with previous studies [36,[38][39][40][41][42] conducted in developing countries including studies done by researchers in Uganda's MRC/UVRI that indicate continuous struggle faced by older adults managing HIV and other chronic diseases. Distance to the facility, cost of traveling to access care, and time [36,42] have all been cited as barriers to accessing HIV care services among HIV infected older adults. These barriers have been exacerbated by persistent verticalization [42,43] of HIV care provision.…”
Section: Discussionsupporting
confidence: 92%
“…A study in rural Kyrgyzstan, for example, found that one in five older people lived more than a 30-minute travel away from a health facility, with access particularly problematic for those with a limiting longstanding illness or disability [39]. The structure of health care provision is also problematic, noted by a study in South Africa of care and treatment for older people (50+) living with both HIV and other chronic conditions, which found that services were typically provided at different health facilities or by different health providers, necessitating multiple patient journeys [40].…”
Section: Ageing Health and Mobilitymentioning
confidence: 99%
“…A final advantage of the TRHC approach is that we expected it would add more information on the social context surrounding testing decisions that is lacking in existing survey data, such as the dynamism of sexual relationships over time [7,32], the potential importance of sexual and marital histories [8], and personal health and wellness [18]. The TRHC demonstrated the distinct advantage of being less structured and more informal than a standard survey interview, but not as free form as a qualitative in-depth interview.…”
Section: Providing Contextmentioning
confidence: 99%
“…Currently, there are limited data on HIV testing and its correlation to health status and sexual relationships for adults transitioning to old age in HIV-endemic, African contexts. Although the HIV epidemic is aging, the focus of HIV data collection, interventions, and programming in Africa has centered on those aged 15-49 [14,15], with only a modest recent increased interest in populations outside this age range [16][17][18]. Overall, studies remain focused on younger adults (e.g., [19,20]).…”
Section: Introductionmentioning
confidence: 99%